Prediction of Flow Resistance using Artificial Neural Network (ANN) in Natural Vegetated Channel - Kamarudzaman, Nur Zahidah (IRC, 2016)
Naturally, vegetated channel has been developed for attenuating the flow in the drainage system. This is considered important as it will work as one of the effective ways to prevent high outflow velocity that could cause flooding and overtop of water at the outflow. The attenuated flow are as the result of the flow-resistant that existed within the drainage system and is manually calculated using Manning’s Roughness Equation, where